Determinación de la capacidad portante del suelo del sector Coperholta, distrito de Tarapoto, provincia de San Martín, región San Martín - Chávez Ramírez, Heleny Del Carmen (2015)
This research was developed in order to study, identify and evaluate soil types that exist in the Coperholta sector and also determine their bearing capacity. By applying the fundamental concepts of soil mechanics. This study was based on the results obtained after running the respective exploration and soil sampling as indicated in the Standard E050 of the National Building Regulations. Exploration samples, which were subjected to the respective trials and the results gave us the physical and mechanical characteristics that have these soils so they can make their classification were obtained, and with the contribution of shear test parameters were obtained the friction angle and cohesion are basic factors to determine the bearing capacity of soils. Thus using the theory of Terzaghi for the type of local failure for square foundations, the bearing capacity of soils Sector Coperholta was calculated. This information being a contribution to the community sector and therefore Coperholta district of Tarapoto. Results that contribute to the practical and scientific to the problem of building without knowing the actual behavior of the soil solutions and anticipating possible settlements and deterioration of buildings, which affect the decoration and therefore the quality of life · owners and users the same. So actively it participated in the production of new knowledge for positive purposes of the community and science. The validation of the hypothesis of this research is achieved with the support of the Statistical Inference! using a multiple regression equation with 95% accuracy, indicating that the values ​​of important capacity of the soils studied are highly significant and allows us to affirm that are sure to build buildings, thus contributing to the community by providing new information on existing bearing capacity In our city.